Potential roles of MEK1 on aging in Argopecten scallops - Yuan, Ke; Lu, Xia; Ning, Junhao; Chen, Min; Wang, Quanchao; Liu, Guilong; Xu, Xin; Xu, He; Wang, Chunde (Frontiers in Marine Science, 2022)
Dual specificity mitogen-activated protein kinase kinase 1 (MEK1) has been found to regulate aging through the Ras/Raf/MEK/ERK cascade in terrestrial animals. However, few reports have focused on MEK1 promoting aging in marine bivalves. In this study, we aimed to examine the potential roles of MEK1 in the regulation of aging in two Argopecten scallops, the bay scallop A. irradians and the Peruvian scallop A. purpuratus, which are closely related but with distinct lifespan. The complete ORFs of AiiMEK1 and ApuMEK1 were both 1209 bp, encoding 403 identical amino acids but with 41 synonymous SNPs, which may have contributed to the different activities of MEK1 in two scallops. Nutrient restriction, one of the most effective non-genetic means of promoting life span, significantly inhibit the expression of AiiMEK1 and ApuMEK1. The response in hepatopancreas of A. irradians to nutrient restriction was more persistently than that in A. purpuratus. RNAi of AiiMEK1 significantly increased the expression of its downstream genes known to favor longevity, such as FoxO and SOD, while decreased the expression of ERK1/2 and the key genes in the mTOR signaling pathway, as well as the β-GAL activity (a marker for senescence). These results indicated that AiiMEK1 may play a negative role in longevity through Ras/Raf/MEK/ERK pathway. Our results may provide new perspective for understanding of the conservative functions of MEK1 in regulation of aging in animals and benefit the genetic selection of scallops.